2010
DOI: 10.3389/neuro.24.001.2010
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the D-Serine-dependent pathway to the cellular mechanisms underlying cognitive aging

Abstract: An association between age-related memory impairments and changes in functional plasticity in the aging brain has been under intense study within the last decade. In this article, we show that an impaired activation of the strychnine-insensitive glycine site of N-methyl-d-aspartate receptors (NMDA-R) by its agonist d-serine contributes to deficits of synaptic plasticity in the hippocampus of memory-impaired aged rats. Supplementation with exogenous d-serine prevents the age-related deficits of isolated NMDA-R-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
210
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(224 citation statements)
references
References 66 publications
10
210
3
1
Order By: Relevance
“…Experimental data confirm this assumption, because the expression of synaptic plasticity, including LTP and LTD of synaptic transmission, is altered in the brain of memory deficient aged animals [42] [43]. Through bioinformation analysis, here from 10 months old to 20 months old ageing process, miR-15b, miR-195 may bind with Grin1 mRNA; miR-30c, miR-125a-5p, miR-125b-5p may bind with Grin2a mRNA; miR-125a-5p, miR-125b-5p, miR-9 may bind with Rhoq mRNA; miR-101b may bind with Grm1 mRNA; and miR-23a, miR-23b, miR-30c may bind with Grm5 mRNA, and these miRNAs may be involved in the regulation of LTP related signal pathways (Table 3, Figure 5(B)).…”
Section: Discussionsupporting
confidence: 64%
“…Experimental data confirm this assumption, because the expression of synaptic plasticity, including LTP and LTD of synaptic transmission, is altered in the brain of memory deficient aged animals [42] [43]. Through bioinformation analysis, here from 10 months old to 20 months old ageing process, miR-15b, miR-195 may bind with Grin1 mRNA; miR-30c, miR-125a-5p, miR-125b-5p may bind with Grin2a mRNA; miR-125a-5p, miR-125b-5p, miR-9 may bind with Rhoq mRNA; miR-101b may bind with Grm1 mRNA; and miR-23a, miR-23b, miR-30c may bind with Grm5 mRNA, and these miRNAs may be involved in the regulation of LTP related signal pathways (Table 3, Figure 5(B)).…”
Section: Discussionsupporting
confidence: 64%
“…Epidemiological and clinical data suggest that nonsteroidal anti‐inflammatory drugs (NSAIDs) are beneficial in the treatment and prevention of AD (Imbimbo et al ., 2010). The protective effects of NSAIDs in AD are due to their anti‐inflammatory properties that inhibit cyclooxygenase‐2 (COX‐2) (McGeer, 2000; van Gool et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular fitness and physical activity have been consistently associated with improved cognitive function [68], strengthened and/or more efficient functional brain activity [917], and increased brain volume in older adults [1822]. More recently, studies have shown that exercise also exerts positive changes on the cerebral vasculature [1, 7, 2328], including preserved CBF in areas associated with aging and AD using ASL [29], higher middle cerebral artery blood flow velocity in young and older adults using transcranial doppler ultrasound [23, 24, 27, 29], and associations between physical fitness, vascular function and cognitive performance in older women [24].…”
Section: Introductionmentioning
confidence: 99%